Factors associated with long-acting and short-acting reversible contraceptives use among 10–24-years-old youths in Lilongwe, Malawi - Maruwo, George Baxton; Ng'ambi, Wingston Felix; Muula, Adamson Sinjani; Zonda, Khumbo; Kachale, Fannie (Frontiers in Reproductive Health, 2022)
Background Evidence suggests that Malawi continues to register substantial progress on key Family Planning (FP) indicators. However, FP adoption is still low among married youth (15–24 years old), only 38% of married girls use modern contraceptive methods coupled with high-unmet needs (22%) in the same age group. Objective Identifying factors associated with long-acting (LARC) and short-acting (SARC) reversible contraceptive use among 10–24-years-old youth in Lilongwe, Malawi. Methodology A retrospective study using secondary data from 64 youth outreach clinic sites in the Lilongwe district. A quantitative approach using secondary data that was analyzed in STATA version 14 was used. A sample of 14,954 youth who accessed FP and Reproductive Health (RH) services during youth outreach clinics were included in the study. Results SARC uptake was higher than LARC (p < 0.01). Of the youths who accessed FP methods, LARC uptake was 25% (n = 3,735). Variations were noted in the uptake of LARC, especially on age, education level, client status occupation, and marital status. Factors associated with LARC uptake varied; new clients were almost twice likely to use LARC (AOR = 1.87, CI: 1.59–2.19, P < 0.01) while youth aged 20–24, the single, and student youth were less likely to use LARC. Compared to young women with formal occupations, students were less likely to use LARC (AOR = 0.30, CI: 0.158–0.58, P < 0.01). Related to the number of living children, youths with a living child were likely to use LARC (AOR = 6.40, CI: 3.91–10.48, P < 0.01). Conclusion This study showed that LARC uptake in youth outreach clinics in Lilongwe is low, though increasing over time. In addition to this, this study shows that SARC uptake is high among youth compared to LARC. Furthermore, LARC uptake varied by age education, client status (new, existing, and unknown client), occupation, number of living children, and marital status, and there were variations in LARC uptake by the clinic. Current outreach services reach youth with LARC services, but gaps exist for underserved youths.